Waterfalls mediate the longitudinal distribution of diadromous predatory fishes structuring communities in tropical, short, steep coastal streams. (10th April 2021) - Ebner, Brendan C.; Donaldson, James A.; Murphy, Helen; Thuesen, Paul; Ford, Andrew; Schaffer, Jason; Keith, Philippe
Abstract: Tropical short, steep coastal streams are typically dominated by diadromous species, especially amphidromous fishes, crustaceans, and molluscs. We undertook a study to determine the distribution of fishes along the stream continuum and determine if substantial natural instream barriers influenced assemblage composition. We surveyed fish assemblages in three short, steep coastal streams in the Australian Wet Tropics by snorkelling and performing single pass counts in each 100‐m section along the entire main channel from the high‐tide mark to the source (or near source: until fish were no longer recorded). A primary focus was mapping the distribution and relative abundance of sicydiine gobies, and we also estimated freshwater crustacean numbers (Caridea: Palaemonidae and Atyidae). In total, 2, 837 individual fish of 25 species were recorded upstream of the high‐tide mark across the three streams and the first records of an additional sicydiine goby ( Smilosicyopus leprurus ) were obtained from continental Australia. Consistent with findings from tropical Pacific island streams, we observed a shift in fish assemblage composition along the elevation gradient and in relation to major instream barriers (e.g. waterfalls >5 m, and high flow chutes across smooth bedrock surfaces). Species richness of diurnal predatory fishes was greatest in the lower course of streams and absent upstream of major instream barriers. Diurnal predatory fishes were, in some instances, found upstream of barriers. Specifically, large adult (>200 mm total length) Kuhlia rupestris (diurnal predators) accessed reaches above challenging sequences of cascades combined with small waterfalls. In contrast, all sizes of that species, adult Kuhlia marginata (>150 mm total length) and a diversity of other diurnal predatory fishes occupied the lower course of streams including upstream of gentle cascade sequences or isolated small waterfalls. Where abundances of diurnal predatory fishes were high, freshwater carideans were rarely observed. Peak densities of carideans were observed upstream of major barriers, with moderate densities in the upper mid‐course in the presence of few Kuhlia spp. The current study demonstrates the value of complete single‐pass surveys of fish assemblages in tropical short, steep coastal streams by revealing the highly localised occupation of particular reaches by rare fishes. It also points towards the importance of stream‐specific characteristics, namely the position of waterfalls in dictating diadromous predator distribution with consequences for community structure, thereby aligning with the Riverine Discontinuum Concept.